KAJIAN TEKNIS PERALATAN TAMBANG UNTUK MEMENUHI TARGET PRODUKSI BATUGAMPING 550.000 TON/BULAN PADA AREA PIT LIMIT (15,15 HA) PT. SEMEN PADANG - Divo Oktoberen; Tamrin Kasim; Ansosry Ansosry (Departemen Teknik Pertambangan FT UNP, 2018)
The process of transporting limestone from Pit Limit area (15,15 ha) to the crusher unit LSC VI (Limestone Crusher VI) using a combination of 1 Excavator Hitachi 2500-6 unit with 4 units of Dumptruck Komatsu HD 785-7. The production target of limestone is 22.000 tons/day or 550.000 tons/month at Pit Limit area (15,15 Ha). Meanwhile, actual productivity of mechanical equipment is only 1.207,5 tons/hour or 18,112.5 tons/day. To realize the planned productivity improvement must be supported by the availability of sufficient mechanical tools to produce raw materials as desired. The efforts made are improve blast fragmentation to simplify the digging process of loading equipment, create a wider loading point, create a flatter haul road and less dusty, improve work efficiency and Effective Utilization (EU), optimize loading time and hauling time, and reduce dumptruck units to 3 units. Then the productivity of mechanical equipment increase to 2.064,83 ton/hour or 30.972,45 ton/day or 774.311,25 ton/month. It means the limestone production target can be achieved at Pit Limit area (15,15 ha). After improvement, the value of Match Factor between 1 unit of excavator and 3 units of dumptruck is MF = 1,1. This combination is more effectively applied than ever before is MF = 0.88.